2016
DOI: 10.1103/physreve.93.033205
|View full text |Cite
|
Sign up to set email alerts
|

Average-atom treatment of relaxation time in x-ray Thomson scattering from warm dense matter

Abstract: The influence of finite relaxation times on Thomson scattering from warm dense plasmas is examined within the framework of the average-atom approximation. Presently most calculations use the collision-free Lindhard dielectric function to evaluate the free-electron contribution to the Thomson cross section. In this work, we use the Mermin dielectric function, which includes relaxation time explicitly. The relaxation time is evaluated by treating the average atom as an impurity in a uniform electron gas and depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Over the years, various theoretical models and approaches have been developed to describe WDM and its properties. Among them are the Ecker-Kröll (EK) model [23], the Stewart-Pyatt (SP) model [24], the average-atom (AA) model [25][26][27][28] and its variation [29], finite-temperature density functional theory (DFT) [30][31][32], frequently in combination with ab-initio molecular dynamics (QMD) [33][34][35][36][37][38][39][40][41], timedependent DFT [42], Monte Carlo molecular dynamics [43], quantum kinetic theory [44,45], and quantum Monte Carlo simulations [46,47]. A recent review highlighting and analyzing the last two topics can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various theoretical models and approaches have been developed to describe WDM and its properties. Among them are the Ecker-Kröll (EK) model [23], the Stewart-Pyatt (SP) model [24], the average-atom (AA) model [25][26][27][28] and its variation [29], finite-temperature density functional theory (DFT) [30][31][32], frequently in combination with ab-initio molecular dynamics (QMD) [33][34][35][36][37][38][39][40][41], timedependent DFT [42], Monte Carlo molecular dynamics [43], quantum kinetic theory [44,45], and quantum Monte Carlo simulations [46,47]. A recent review highlighting and analyzing the last two topics can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%